Short-selling on corporate investment: Korean evidence - Sang-Giun Yim (Global Business & Finance Review (GBFR), 2023)
Purpose: Prior studies suggest that an informative stock price helps corporate investment decisions. Since short-selling improves the informativeness of stock prices, short-selling could influence corporate investment. This study examines this conjecture. Design/methodology/approach: Using KOSPI-listed firm data, this study examines whether short-selling affects quantitative aspects, that is, amount, and qualitative aspects, that is, risks and profitability, of R&D or capital expenditure. Findings: The results show a distinct contrast between the two types of investment. After short-selling, a decrease in R&D investment i s observed; however, capital e xpenditure i ncreases i n firms that i nvest much i n capital expenditure. A post-short-selling increase in R&D increases firm risk, but capital expenditure does not. Post-shortselling R&D investment is tied to long-term profitability; however, except for large firms, capital expenditure does not contribute to the increase in long-term profitability. Research limitations/implications: This study provides supporting evidence that improved informativeness of stock prices improves investment efficiency, not only through R&D investment but also through capital expenditure. However, by examining the topic in the big picture, this study leaves out the influence of several factors that can affect investment decisions. Originality/value: This is one of the rare studies that examines the real impact of short-selling.
Keywords: 650; Short-selling; Corporate Investment; R&D; CAPEX; Risk of Investment; Profitability of Investment